Who Were the Faithful?: Nicholas of Cusa's De Pace Fidei. Issue 159 (1st July 2019) - Benjamin, Andrew
Abstract : The aim of this paper, which more generally is a contribution to political theology, is to show in what way the conception of peace in Nicholas of Cusa's De Pace Fidei is dependent upon a specific philosophical anthropology. Within it any link between human being and law is replaced by the subject of faith. Central to the argument is demonstrating the ways in which this anthropological position is necessarily interarticulated with the larger metaphysical positions that are advanced across a range of Cusanus' texts.